Prosthetic rehabilitation of patients with history of moderate to severe periodontitis: a long‐term evaluation. (12th June 2013) - Graetz, Christian; Schwendicke, Falk; Kahl, Maren; Dörfer, Christof E.; Sälzer, Sonja; Springer, Claudia; Schützhold, Svenja; Kocher, Thomas; König, Jörgen; Rühling, Andreas
Abstract Objectives Long‐term outcomes of conservative periodontal and prosthetic treatment of patients with moderate to severe periodontitis were to be evaluated. Groups of younger (YG) and middle‐aged patients (MG) were to be compared regarding survival of fixed and removable dental prostheses (FDP, RDP) inserted after active periodontal therapy (APT). In addition, functional‐occlusal status over more than 10 years of supportive periodontal therapy (SPT) was analysed. Methods The present multi‐case‐series retrospectively analysed data of 68 patients (34 YG and 34 MG) who had received APT and regular SPT ≥10 years. Tooth loss, occlusal status and survival and complications of prosthetics were evaluated descriptively and comparatively (t‐test). Results There was no statistical difference between YG and MG concerning tooth loss/year (p > 0.05). Functional‐occlusal status was retained during SPT in 75% and 69% of YG and MG. Restorations inserted after APT showed high survival for both age groups (100%). Mean survival time until the last SPT visit was 15.2 and 11.6 years for FDP and RDP in YG, and 12.5 and 13.1 years in MG. Conclusions Prosthetic restorations in both younger and middle‐aged patients with severe periodontitis showed high survival, if pre‐prosthetic APT and regular SPT had been performed.